2020
DOI: 10.1063/5.0008939
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension driven flow of blood in a rectangular microfluidic channel: Effect of erythrocyte aggregation

Abstract: Microfluidic platforms have increasingly been explored for in vitro blood diagnostics and for studying complex microvascular processes. The perfusion of blood in such devices is typically achieved through pressure driven setups. Surface tension driven blood flow provides an alternative flow delivery option, and various studies in the literature have examined the behaviour of blood flow in such fluidic devices. In such flows, the influence of red blood cell (RBC) aggregation, the phenomenon majorly responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Therefore, if aggregation increases, then blood viscosity increases as well and the shear-thinning behavior of blood is altered. Numerical studies have demonstrated the effects of aggregation in blood viscosity [120,122,[152][153][154] and experimental studies have observed that RBCs' deformability induces cell aggregation during flow in microcapillaries, allowing the formation of clusters of cells [98,155,156]. Moreover, the aging of storaged RBCs also contributes to the increase in aggregation and affects its viscosity.…”
Section: Comparison With Numerical Results Of the Collective Behavior...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if aggregation increases, then blood viscosity increases as well and the shear-thinning behavior of blood is altered. Numerical studies have demonstrated the effects of aggregation in blood viscosity [120,122,[152][153][154] and experimental studies have observed that RBCs' deformability induces cell aggregation during flow in microcapillaries, allowing the formation of clusters of cells [98,155,156]. Moreover, the aging of storaged RBCs also contributes to the increase in aggregation and affects its viscosity.…”
Section: Comparison With Numerical Results Of the Collective Behavior...mentioning
confidence: 99%
“…Eventually, high-speed and high-resolution cameras, with an enhanced sensitivity and mounted to an optical microscope, enabled velocity measurements of such small-scale flows. In this aspect, several techniques have been developed to measure the velocity fields of blood and RBCs at the microscale, such as µPIV (microparticles image velocimetry) or PTV (particle tracking velocimetry) and wavelet-based optical flow velocimetry (wOFV) [95][96][97][98][99]. 5), is averaged for different initial conditions of the RBC.…”
Section: Hemodynamics and Hemorheology For A Single Cellmentioning
confidence: 99%
“…These alterations contribute to a reduction of mass transport and interrupt the blood flow in capillary vessels. To effectively detect changes in blood samples from a physical point of view, several rheological properties (i.e., viscosity [ 3 , 4 , 5 , 6 ], viscoelasticity [ 7 ], red blood cell (RBC) deformability [ 8 , 9 , 10 , 11 , 12 , 13 ], RBC aggregation [ 14 , 15 , 16 , 17 ], RBC sedimentation rate [ 18 , 19 ], and Hct [ 20 ]) have been measured for screening or diagnosing various diseases, including coronary heart disease, hypertension, diabetes [ 21 ], sickle cell anemia [ 22 , 23 ], and malaria. Plasma protein (i.e., fibrinogen) contributes to increasing RBC aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Although a blood flow rate can be estimated consistently with micro-particle image velocimetry (PIV) [ 31 ], it is very difficult to obtain an accurate flow rate of a blood sample. The flow rate obtained with micro-PIV varies strongly with several factors, such as flow rate, hematocrit, diluent, RBC aggregation, and RBC deformability [ 13 , 14 , 29 ]. Whenever blood viscosity is to be monitored, tedious calibration procedures are required in advance using the same blood sample.…”
Section: Introductionmentioning
confidence: 99%
“…Methods such as image segmentation allow the identification of structures with specific characteristics [ 25 , 26 ]. To accommodate the blood sample to be processed, simple microfluidic configurations are often used, offering several advantages [ 27 , 28 , 29 , 30 ]. Other techniques, such piezocoagulography, have been also utilized for blood coagulation, showing also the possibility of studying the initial stage of fibrin formation in the clotting process [ 31 ].…”
Section: Introductionmentioning
confidence: 99%